PREVENTIVE EFFECT OF CYCAS REVOLUTA IN 1,2-DIMETHYLHYDRAZINE-INDUCED COLON CANCER IN WISTAR RAT MODEL - Bera, Samit; Das, Bhaskar; De, Arnab; Samanta, Amalesh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The aim of this study was to evaluate the colon cancer protective activity of Cycas revoluta (Cycadaceae). Methods: Methanolic extracts of C. revoluta (MECR) were assessed for total polyphenols and total flavonoids content. For the in vivo study, animals were divided into five groups (n=6). Group I serves as control which received 0.25% carboxymethyl cellulose solution. Groups II-V were treated with 1,2-dimethylhydrazine (DMH) which was given at the dose of 20 mg/kg b.w., s.c. once a week for 4 consecutive weeks. Aqueous suspension of MECR at a dose of 200 mg/kg/day and 400 mg/kg was administered orally to the animals in Groups III-IV every day for 16 weeks. Group V received 5-fluorouracil (5-FU) as a standard drug at a dose of 10 mg/kg b.w., per day s.c. for 16 weeks. After that, animals are sacrificed and colons are taken separately to evaluate biochemical parameters and morphological and histopathological changes. Results: MECR contains total polyphenols (6.3Â±0.09 mg of gallic acid equivalent /g) and total flavonoids (4.6Â±0.06 mg of rutin equivalent/g). The in vivo study revealed that superoxide dismutase (SOD), catalase, and reduced glutathione (GSH) activity were decreased in DMH Group. All these parameters were restored significantly (p<0.05) toward the near normal value on supplementation with MECR (200 and 400 mg/kg b.w.) to DMH-treated rats (Groups III and IV). In Group V, the synthetic standard drug 5-FU (10 mg/kg b.w.) also increases the activities of SOD, CAT, and GSH significantly (p<0.05) more in DMH-treated rats. Conclusions: It can be concluded that MECR protects rat from DMH-induced colon cancer.